LE CINÉMA COMME MÉDIA CULTUREL ET ÉDUCATIF DANS L’ENSEIGNEMENT-APPRENTISSAGE DES LANGUES ÉTRANGÈRES - Paola APPETITO (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
Cinema as a Cultural and Educational Medium in Teaching / Learning Foreign Languages. Cinema is one of the most effective and authentic materials that can convey language, culture and art at the same time. The teaching-learning of film language is part of a media education that has become necessary today. Our everyday environment constantly exposes the individual to media messages, and modern dissemination techniques increase their impact remarkably. Thus, we must try to set up a contextualized learning of languages and cultures, aiming at increased awareness of the different media languages. First, our study tries to evaluate the level of media education in the European context, especially in France, then to provide teachers and language learners with useful websites and a resource directory offering them a starting point to using cinema in school and academic contexts.